(untitled) - Sanderson, Paul (Cambridge, UK, 1999)
Contents: Headlines; articles; photographs; advertisements; horoscopes; problem page letters; TV guides; cartoons and strip cartoons; weather forecasts; the whole newspaper.
Keywords: language arts,Newspapers in education